2016
DOI: 10.3390/ma9040231
|View full text |Cite
|
Sign up to set email alerts
|

Review on Microwave-Matter Interaction Fundamentals and Efficient Microwave-Associated Heating Strategies

Abstract: Microwave heating is rapidly emerging as an effective and efficient tool in various technological and scientific fields. A comprehensive understanding of the fundamentals of microwave–matter interactions is the precondition for better utilization of microwave technology. However, microwave heating is usually only known as dielectric heating, and the contribution of the magnetic field component of microwaves is often ignored, which, in fact, contributes greatly to microwave heating of some aqueous electrolyte s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
245
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 513 publications
(285 citation statements)
references
References 127 publications
2
245
0
5
Order By: Relevance
“…In order to overcome this barrier, microwave irradiation can be used as an effective tool in the catalysis. Microwave irradiation heating has several advantages over conventional radiant heating, such as high heating rate, uniform heating, and less energy requirement, resulting in a rapid temperature rise of the entire reaction mixture . Therefore, the microwave irradiation has emerged as a powerful technique towards sustainable chemistry because it offers efficient, safe, and clean eco‐friendly processes…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to overcome this barrier, microwave irradiation can be used as an effective tool in the catalysis. Microwave irradiation heating has several advantages over conventional radiant heating, such as high heating rate, uniform heating, and less energy requirement, resulting in a rapid temperature rise of the entire reaction mixture . Therefore, the microwave irradiation has emerged as a powerful technique towards sustainable chemistry because it offers efficient, safe, and clean eco‐friendly processes…”
Section: Methodsmentioning
confidence: 99%
“…Microwave irradiation heating has several advantages over conventional radiant heating, such as high heating rate, uniform heating, and less energy requirement, resulting in a rapid temperature rise of the entire reaction mixture. 5 Therefore, the microwave irradiation has emerged as a powerful technique towards sustainable chemistry because it offers efficient, safe, and clean eco-friendly processes. 6 We have previously reported that silica gel-supported Nheterocyclic carbene (NHC)-Pd complex 1 can serve as an active catalyst for the Suzuki reaction.…”
mentioning
confidence: 99%
“…But microwave energy, with a frequency of 2.45 GHz, is well known to have a significant effect on the rate of various processes in the chemical and food industry. [28] It is important to recognize that the energy delivered by microwaves is insufficient for breaking covalent chemical bonds. During microwave at highfrequency heating, many material properties affect the heating performance.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, the energy is transferred through the material by direct microwave-matter coupling, not as a thermal heat ux. Consequently, the rate of heating is often high, and the uniformity of heat distribution is greatly improved [9]. All these features undeniably contribute to the high e ciency of the microwave thermal process.…”
Section: Introductionmentioning
confidence: 99%